Exosomes of Human Umbilical Cord MSCs Protect Against Hypoxia/Reoxygenation-Induced Pyroptosis of Cardiomyocytes via the miRNA-100-5p/FOXO3/NLRP3 Pathway - Liang, Chenyu; Liu, Yang; Xu, Huifeng; Huang, Junling; Shen, Yi; Chen, Faxiu; Luo, Ming (Frontiers in Bioengineering and Biotechnology, 2021)
Background Acute myocardial infarction (AMI) is one of the leading causes of morbidity and death worldwide. Studies have indicated that microRNAs in mesenchymal stem cell (MSC)-derived exosomes are crucial for treating various diseases. Methods Human umbilical cord MSC (hucMSC)-derived exosomes (hucMSC-exo) were isolated and used to treat cardiomyocytes that underwent hypoxia/reoxygenation (H/R) injury. Bioluminescence assessment was used to study binding of miRNA to its targeting gene. Results We found that H/R decreased the viability of AC16 cells, increased the expression of NLRP3, and activated caspase-1(p20) and GSDMD-N as well as release of IL-1β and IL-18, and such effects were abolished by administration of hucMSC-exo. Administration of exosomes from negative scramble miRNA (NC)-transfected hucMSCs blocked H/R-caused lactate dehydrogenase release, pyroptosis, and over-regulation of NLRP3 and activated caspase-1(p20) and GSDMD-N as well as release of IL-1β and IL-18. More importantly, in comparison to exsomes from NC-transfected hucMSCs, exsomes from miR-100-5p-overexpressing hucMSCs had more obvious effects, and those from miR-100-5p-inhibitor-transfected hucMSCs showed fewer effects. Functional study showed that miR-100-5p bound to the 3’-untranslated region (3’-UTR) of FOXO3 to suppress its transcription. Moreover, overexpression of FOXO3 abolished the protective effects of miR-100-5p. Conclusion Enriched miR-100-5p in hucMSC-exo suppressed FOXO3 expression to inhibit NLRP3 inflammasome activation and suppress cytokine release and, therefore, protected cardiomyocytes from H/R-induced pyroptosis and injury.